EFFECT OF THE PHYTOESTROGEN DAIDZEIN ON TESTICULAR CELL FUNCTIONS - Monsees, T. K.; Bittorf, K.; Hinkel, S.; Hayatpour, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The soy bean isoflavone daidzein has weak estrogenic properties. Estrogens can disturb male reproduction by inhibiting steroidogenesis in Leydig cells. They may also cause decreasing sperm counts by affecting Sertoli cells which are crucial in spermatogenesis. We investigated the effect of estrogenic compounds on testicular cells in vitro. Cultures of rat Sertoli (SC) or Leydig (LC) cells were incubated with estrogens (nM to µM) for 3 d. Cytotoxicity, production of lactate and secretion of inhibin B (SC) or steroids (LC) were determined. 0.1-1 µM of estrogen did not alter any Sertoli cell parameter investigated. At higher concentrations (3-36 µM), only daidzein significantly reduced cell viability whereas ethinylestradiol significantly enhanced secretion of lactate and inhibin B. In contrast, bisphenol-A reduced inhibin levels. In Leydig cells, a dose-dependent decrease in progesterone and testosterone production was induced by nM of estradiol and ethinylestradiol, or µM of daidzein. Cell viability was not affected. Estrogen receptors are present in Sertoli and Leydig cells. Inhibition of LC testosterone synthesis by estradiol and ethinylestradiol was observed at nM concentrations and thus possibly be related to genomic effects. Daidzein acted only at µM levels. Here, a non-genomic mechanism, e.g. by competitive inhibition of enzymes involved in steroidogenesis is likely. A receptor-independent action may also be responsible for the observed effects of daidzein, ethinylestradiol, and bisphenol A on Sertoli cells. A daily intake of 1 mg/kg BW (= 3.9 µM) of daidzein is regarded as safe. This concentration, however, caused a significant reduction of androgens in our test system.